EXOSC4 functions as a potential oncogene in development and progression of colorectal cancer. Issue 12 (21st September 2018) - Pan, Yi; Tong, Joanna H. M.; Kang, Wei; Lung, Raymond W. M.; Chak, Wing Po; Chung, Lau Ying; Wu, Feng; Li, Hui; Yu, Jun; Chan, Anthony W. H.; To, Ka Fai
Abstract : Colorectal cancer (CRC) is a heterogeneous disease with complex mechanisms of pathogenesis. Classification systems have been proposed based on molecular features of tumors in clinical practice. Thus, more molecular markers associated with development and progression of CRC might serve as useful tools for early diagnosis even for providing more accurate molecular classification. Frequent gain of chromosome 8q was detected in CRC by array‐CGH and overexpression of exosome component 4 (EXOSC4) in this region was revealed by expression microarray analysis. Through qRT‐PCR and immunohistochemistry (IHC) analysis, EXOSC4 showed increased expression in CRC cell lines and clinical specimens. Higher expression of EXOSC4 was more often detected in left side, and correlated with BRAF wild type, MSI‐low or MSS, CIMP‐low, and MLH1‐no‐silence CRC patients. Functionally, EXOSC4 overexpression increased early tumorigenic capacity by promoting cell proliferation and monolayer colony formation, enhancing cell invasion and migration study and accelerating xenograft formation in nude mice. While EXOSC4 knockdown exhibited anti‐oncogenic role such as inhibiting cell proliferation and invasion. EXOSC4 inhibition also resulted in G1 phase cell cycle arrest. For the downstream signaling analysis, EXOSC4 was found to be involved in multiple signaling pathways such as cell cycle, p53 pathway and Wnt pathway. In summary, our findings demonstrated the oncogenic role of EXOSC4 in development and progression of CRC. Deep understanding of EXOSC4 as a potential diagnostic molecular biomarker will provide clinical translational potential for intervention therapy.